RESTORATIVE JUSTICE SEBAGAI ALTERNATIF PEMENUHAN KEADILAN TERHADAP ANAK KORBAN TINDAK PIDANA PERKOSAAN - Artisa Meyta Mulandri (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2020)
Artisa Meyta Mulandri, Ismail Navianto, Mufatikhatul Farikhah Fakultas Hukum Universitas BrawijayaJl. MT. Haryono No. 169 Malange-mail : ameyta8@gmail.comAbstrak Permasalahan dalam penelitian ini adalah belum terpenuhinya keadilan bagi anak korban perkosaan. Anak yang menjadi korban membutuhkan perlindungan hukum berupa keadilan sebagai haknya. Maka dari itu perlu ada alternatif untuk memenuhi keadilan. Penelitian ini menggunakan metode penelitian yuridis normatif dengan metode pendekatan perundang-undangan (statute approach) dan pendekatan konseptual (conseptual approach). Berdasarkan hasil penelitian dengan metode di atas, dapat diketahui bahwasannya pemenuhan keadilan bagi anak korban tindak pidana perkosaan belumlah dapat dikatakan adil. Salah satu hak bagi anak yang terlibat dengan hukum adalah mengutamakan kepentingannya, kepentingan anak disitu berupa bentuk kebebasan, persamaan, dan kesejahteraan. Maka dari itu perlu ada alternatif lain guna memberikan pemenuhan keadilan bagi anak korban. Alternatif pemenuhan keadilan berdasar prinsip restorative justice antara lain melakukan terapi trauma dan terapi psikis bagi anak korban, kewajiban perwakilan masyarakat untuk ikut serta dalam proses diversi, dan pendampingan yang dilakukan oleh psikolog dengan anak korban. Alternatif tersebut dilaksanakan dengan menggunakan prinsip restorative justice dimana prinsip tersebut memiliki beberapa bentuk antara lain yaitu dengan Victim Offender Mediation, Conferencing, Circles, dan Reparative Board / Youth Panel.Kata kunci : pemenuhan keadilan, alternatif pemenuhan keadilan, restorative justiceÂ Abstract The issue studied is regarding the unfulfilled justice for young victims in a rape. Children becoming victims in such a crime need legal protection such as justice as their rights. Therefore, some alternating solutions are present to provide justice. This research employed normative-juridical method, statute, and conceptual approaches. The research result reveals that fulfilling justice for children as victims in a rape is not fairly performed. To fulfil the rights of the children, their interest should be put in priority, where they have their rights to freedom, equality, and welfare. Thus, alternative is needed to protect children as the victims. This alternative follows the principle of restorative justice involving trauma and psychological therapies for the victims, participation of the members of society in diversion process, and counselling given by a psychologist. Those measures are taken based on the principle of restorative justice that comprises the following forms such as victim offender mediation, conferencing circles, and reparative board/youth panel.Keywords: Fulfilling justice, alternative of justice fulfilment, restorative justiceAbstract The issue studied is regarding the unfulfilled justice for young victims in a rape. Children becoming victims in such a crime need legal protection such as justice as their rights. Therefore, some alternating solutions are present to provide justice. This research employed normative-juridical method, statute, and conceptual approaches. The research result reveals that fulfilling justice for children as victims in a rape is not fairly performed. To fulfil the rights of the children, their interest should be put in priority, where they have their rights to freedom, equality, and welfare. Thus, alternative is needed to protect children as the victims. This alternative follows the principle of restorative justice involving trauma and psychological therapies for the victims, participation of the members of society in diversion process, and counselling given by a psychologist. Those measures are taken based on the principle of restorative justice that comprises the following forms such as victim offender mediation, conferencing circles, and reparative board/youth panel. Keywords: Fulfilling justice, alternative of justice fulfilment, restorative justice